Когнітивні аспекти теорії модальності - Бріцин, В.М.; Мозгунов, В.В. (Мовознавство, 2013)
Антропоцентрична парадигма опису мови зумовила помітні зміни в поняттєво-терміно-логічному апараті лінгвістичних досліджень, спричинила нову інтерпретацію багатьох базових мовних категорій, зокрема категорії модальності. У статті сформульовано нову когнітивну теорію модальності, показано можливості її застосування в текстовому аналізі, задекларовано її застосовність для пояснення особливостей багатьох мовних категорій: категорії предикативності, категорії метафори, категорії вставленості тощо. Anthropocentric paradigm of language description led to significant changes in the conceptual
and terminology of linguistic research, caused a new interpretation of many basic linguistic categories,
including categories of modality. The paper formulates a new cognitive theory of modality,
demonstrates the possibility of its application in text analysis, declares its applicability to explain
many features of linguistic categories: predictive category, category of metaphor, snterposing
cateory etc.
Is debatable aspects of determining of the modality nature, proposed by V. V. Vinogradov,
V. Z. Panfilov, A. V. Kolshanskyi et al.
Anthropocentric paradigm of linguistic research states at the 80-ies of the last century. Most definitely
it is implemented on the material of Slavic languages lexical resources, in turn, the study of
grammatical structure is at an early stage. However, by W. von Humboldt noted that language is not
a product of activity, but the activity itself.
Real life language, speech is no less important object of study than the totality of language
means, abstracted from speech. The defined category of subjective modality seems to be poorly delineated
with the category of evaluation.
Submitted material exemplifies artificiality of modality’s traditional concept, illustrates its internal
contradictions. Modal interpretation of simple sentences in the indicative mood allows them
not only and not so much a reflection of reality function, as transfer function of the inner world of the
speaker.
Cognitive approach to the category of modality is important not only for linguistics, but also for
the theory of language development, the interaction of language etc.
The approach to the category of modality is important not only for linguistics, for example, the
theory of language development, interaction, language and thinking styles theory to explain the features
of linguistic categories, including categories of metaphor. He has considerable potential for interpretive
research in the field of literature, philosophy, psychology.